Effectiveness of maternity waiting homes in increasing utilization of facility-based delivery: A systematic review - Absa Secka; Samsriyaningsih Handayani (Intelektual Pustaka Media Utama, 2021)
To reduce the second delay contributing to maternal mortality, maternity waiting homes have been recommended for implementation especially in remote areas to help improve access to facility-based skilled delivery. Evidence of its effectiveness, however, is limited. This systematic review, therefore, aims to assess the effectiveness of the Maternity waiting home strategy in increasing utilization of facility delivery. Search for relevant articles was conducted on PubMed, Scopus, Google Scholar, Ebscohost, and Science Direct from database inception to March 30, 2021. Two reviewers independently screened the articles and assessed the quality of the studies. The identified maternity waiting home interventions and their effectiveness in improving facility-based delivery uptake were narratively synthesized and reported following the preferred reporting items for systematic reviews and meta-analysis reporting guidelines. The search yielded 670 articles of which five studies fulfilled the inclusion criteria. The three of five studies revealed that there is a significant association between Maternity waiting home use and utilization of facility-based delivery. The quality of the Maternity waiting homes significantly improved facility-based delivery uptake. Maternity Waiting Homes appear to be promising in decreasing barriers to skilled delivery attendance however the quality of evidence is low. More interventional studies of robust design are needed to clearly demonstrate its effectiveness.